Pentoxifylline and prevention of contrast-induced nephropathy: Is it efficient in patients with myocardial infarction undergoing coronary angioplasty? - Ali Eshraghi; Roya Naranji-Sani; Hourak Pourzand; Mohammad Vojdanparast; Negar Morovatfar; Javad Ramezani; Ramin Khamene-Bagheri; Pouya Nezafati (ARYA Atherosclerosis, 2016)
BACKGROUND: Contrast-induced nephropathy (CIN) is a major concern following procedures with applying iodinated contrast media. The basis prevention of CIN is hydration and to avoid hypovolemia. We aimed to evaluate the efficacy of pentoxifylline (PTX) for the prevention of CIN in patients with myocardial infarction (MI) undergoing coronary angioplasty. METHODS: This prospective, single-blind, randomized clinical trial study was performed on 175 (127 men) of MI patients undergoing routine treatment. Patients were assigned randomly to the control (n = 84) and study groups (n = 91). In our study group, patients received 400 mg/3 times a day from 24 hours before to 24 hours after coronary angiography. In addition, before the procedure and after 48 hours from the procedure, serum creatinine was measured. RESULTS: CIN occurred in 14 patients (8.0%); 8 controls (9.5%) and 6 patients (6.6%) in the PTX group )P = 0.475) showing PTX to have no significant effect on CIN [P = 0.750, odds ratio = 0.82 (confidence interval = 0.24-2.8)] though a significantly different volume of contrast was used between the groups (231.29 ± 105.10 mm3 and 190.88 ± 75.82 mm3; P = 0.005, respectively). CONCLUSION: There was no significantly different occurrence of CIN on patients with MI, undergoing coronary angioplasty, but its relatively lower rate in PTX group would recommend the prophylactic oral use of PTX for CIN prevention.